Student learning guide [for] Effective marketing : creating and keeping customers - Zikmund, William G. (South-Western College, 1998)
The nature of marketing. Marketing management. Environmental forces in a diverse world. The microenvironment in an Era of global competition. Global information systems and marketing research. Consumer behavior. Business markets and organizational buying. Market segmentation, targeting, and positioning strategies. Basic concepts about goods, services and positioning strategies...